Study on the Full‐Cycle Stress Evolution Law and Reasonable Size of Isolated Coal Pillar - Xiao‐Xiang Wei; Qing‐Long Yun; Jing Wu; Xiao‐He Wang; Yin‐Wei Wang (Energy Science & Engineering)
ABSTRACT To study the stress distribution law under different mining times and spaces of the protected coal pillar in the isolated working face, this paper takes a coal mine in Shanxi as the engineering background and adopts numerical simulation and theoretical analysis to obtain the stress distribution law of protecting coal pillar in the isolated working face during the tunneling period and the mining period of the working face, and proves the reasonable size of protecting coal pillar. The results show that the vertical stress and maximum principal stress increase correspondingly with the decrease of the protective coal pillar size under both stages, and the minimum value of the minimum principal stress occurs on the 8 m protective coal pillar; The values of the principal stress ratio and the principal stress deflection angle do not differ greatly in the protection of the coal pillar, and the fluctuation of the values is mainly concentrated in the vicinity of the back‐mining roadway; The second invariant of bias stress (J2) is mainly concentrated in the protective coal pillar near the side of the extraction zone, when the size of the protective coal pillar is reduced to 10 m, the J2 on the side of the extraction zone and the J2 on the side of the roadway are connected, and the whole protective coal pillar is under the influence of J2, which is basically the same as the damage pattern of the plastic zone; Based on the formula of limit balance theory to calculate the elastic core width of different sizes of protective coal pillars, and combined with the results of numerical simulation analysis, it finally concluded that the reasonable size of the protective coal pillar of this isolated island working face is 15 m.